The Effects of Local Wisdom-Based Group Counseling using Macapat Sinom on High School Students: Cultural Pride in Counseling Implementation - Pranowo, Taufik Agung; Susanto, Eko (Universitas Negeri Padang, 2023)
The purpose of this study is to ascertain how group counseling based on traditional Macapat Sinom wisdom affects students. This study used a case study research design in conjunction with a qualitative methodology. To gather data, in-depth interviews were conducted. This study focuses on students, class teachers, and guidance and counseling professionals. 1) Data collection, 2) Data reduction, 3) Data presentation, and 4) Conclusion are all included in data analysis. Triangulation of sources was used to determine the data's validity. According to this study, students learn about the moral lesson found in macapat sinom. Student comprehend the significance of classic literature. The values of the local culture and how they can influence an individual's identity are better understood by the students. The impact of group counseling based on traditional Macapat Sinom wisdom is increasing students' cultural pride, according to the conclusion.